HyPRP1 Gene Suppressed by Multiple Stresses Plays a Negative Role in Abiotic Stress Tolerance in Tomato - Li, Jinhua; Ouyang, Bo; Wang, Taotao; Luo, Zhidan; Yang, Changxian; Li, Hanxia; Sima, Wei; Zhang, Junhong; Ye, Zhibiao (Frontiers in Plant Science, 2016)
Many hybrid proline-rich protein (HyPRP) genes respond to biotic and abiotic stresses in plants, but little is known about their roles other than as putative cell-wall structural proteins. A HyPRP1 gene encodes a protein with proline-rich domain, and an eight-cysteine motif was identified from our previous microarray experiments on drought-tolerant tomato. In this study, the expression of the HyPRP1 gene in tomato was suppressed under various abiotic stresses, such as drought, high salinity, cold, heat, and oxidative stress. Transgenic functional analysis showed no obvious changes in phenotypes, but enhanced tolerance to various abiotic stresses (e.g., oxidative stress, dehydration, and salinity) was observed in RNAi transgenic plants. Interestingly, several SO2 detoxification-related enzymes, including sulﬁte oxidase, ferredoxins (Fds), and methionine sulfoxide reductase A (Msr A), were revealed in HyPRP1-interacting proteins identified by Yeast Two-Hybrid screening. More sulfates and transcripts of Msr A and Fds were accumulated in HyPRP1 knockdown lines when wild-type plants were exposed to SO2 gas. Our ﬁndings illustrate that the tomato HyPRP1 is a negative regulator of salt and oxidative stresses and is probably involved in sulﬁte metabolism.